PENGUATAN KELEMBAGAAN DESA DALAM MEWUJUDKAN OTONOMI DI DESA-DESA PESISIR STUDI DI DESA SOKOP KECAMATAN RANGSANG PESISIR KABUPATEN KEPULAUAN MERANTI - Tinov, MY Tiyas; Handoko, Tito (Universitas Riau, 2016)
This study examines the institutional strengthening Sokop village in the district of MerantiIslands. The village of institutional issues Sokop be a reflection of the condition of the villagesare located in coastal areas and outer islands in Indonesia. Limitations accessibility of informa-tion, transport and communication are key issues faced by the region (read-Village Sokop) sothat the development of institutional capacity and its derivatives is not as advanced and as fastas the accessibility of the region are within easy reach. By putting itself on the theoretical frame-work of institutional strengthening these studies focus to see phenomena institutional VillageSokop especially from the aspect of good governance and administrative capacity Sokop Vil-lage Government officials. This study used a qualitative approach and to optimize the study, theauthors used the strategy phenomenology.The results of this study indicate that the institutional capacity of the village governmentSokop not support in efforts to achieve regional autonomy, it is characterized by weak institu-tional role Desa Sokop in building independence of the village, institutional structuring andmanagement of village governance, weak financial management, and lack of community par-ticipation in development village (participatory development).